Bioengineering in women's health: part I. Issue 4 (14th June 2019) - Miller, Kristin S.; Myers, Kristin; Oyen, Michelle
Abstract : This theme issue of Interface Focus is the first of two sets of articles on the topic of bioengineering in women's health. Although there is a long history of collaboration between engineers and medical professionals in orthopaedics and cardiovascular medicine, there has been growing interest in the last decade for interdisciplinary collaborations in other areas of medical science. This growth is particularly true in the case of women's health, a traditionally underserved area of research in the scientific community where fundamental knowledge of female physiology is still needed. Women's health is a broad category encompassing reproduction, fertility, maternal health, normal and abnormal pregnancy and the sequelae associated with a difficult childbirth. Women's health also includes sex-associated pathology associated with cancer, pain, cardiac disease, osteoporosis and other diseases. This list is not exhaustive with new scientific frontiers developing based on the evolving discourse of medicine for all. This first issue in the series focuses on bioengineering advances in the study of the non-pregnant woman, and the articles highlight important developments in pelvic floor disorders, biomedical devices, fertility, breast implant failure and breast cancer. The second issue in the series focuses on pregnancy.